AN ANALYSIS OF THE STUDENTS’ ABILITY IN USING ADVERB OF FREQUENCY IN SIMPLE PRESENT TENSE: A STUDY ON THE FIRST YEAR STUDENTS OF SMA N 7 PADANG IN ACADEMIC YEAR 2009/2010 - Novi Riani (Institut Agama Islam Yasni Bungo, 2017)
The objective of this research was to describe the ability of the first year students of SMA N 7 Padang to use adverb of frequency in simple present tense. The population of this research was the first year students of SMA N 7 Padang in academic year 2009/2010. There were 305 students as members of population. In selecting the sample, the researcher used cluster random sampling. Finally, class X2 that consisted of 36 students was a sample of this research. in technique of collecting data, the researcher used structure test that consisted of 40 items as instrumenataion. Before giving the test to the sample, the test was tried out. Then, the researcher analyzed the data by counting standard deviation (SD) and mean (M). Generally, the result of this research showed that the ability of the first year students of SMA N 7 Padang to use adverb of frequency in simple present tense was moderate. It was proved by the fact that 6 students (16,7%) had high ability, 23 students (63,9%) had moderate ability, and 7 students (19,4%). Specifically, the ability of the students to use adverb of frequency in affirmative sentence of smple present tense was moderate since 25 students (69.4%) had moderate ability. The ability of students to use adverb of frequency in negative sentence of simple present tense was moderate. It was due to the fact that 22 students (61.1%) had moderate ability, the ability of students to use adverb of frequency in interrogative sntece of smple present tense was moderte. it was due to the fact that 16 students (44.4%) had moderate ability. Keywords: Ability, Adverb of Frequency, Present Tense.